Facile synthesis of medium molecular weight polyisobutylene with remarkable efficiency employing the complexed BF3·EtOH/TiCl4·H2O initiating system. (November 2019) - Jin, Yulong; Dong, Ke; Xu, Linfeng; Guo, Xing; Cheng, Ruihua; Liu, Boping
Graphical abstract: Highlights: Novel complexed catalyst BF3 ·EtOH/TiCl4 ·H2 O was synthesized for the cationic polymerization of isobutylene. Remarkable synergistic effect was produced in the complexed catalyst. Medium molecular weight polyisobutylene (MPIB) could be facilely synthesized generally. Abstract: In this work, a novel complexed catalyst system consisting of BF3 ·EtOH/TiCl4 ·H2 O was synthesized and systemically investigated. It revealed that notable synergistic effect could be observed for the complexed catalyst in the cationic polymerization of isobutylene (IB), reflected by the much higher activity of the complexed one (>5.4 × 10 3  kgPIB·mol −1 (BF3  + TiCl4 )·h −1 ) than those of BF3 ·EtOH (<2.6 × 10 3  kgPIB·mol −1 BF3 ·h −1 ) and TiCl4 ·H2 O (<10 kgPIB·mol −1 TiCl4 ·h −1 ) under the optimized reaction conditions. Thus with lower than 3 mmol·L −1 Lewis acids (BF3  + TiCl4 ), reasonable monomer conversion higher than 80% could be achieved at high monomer concentration (4–6 mol·L −1 ) in 15 min with the complexed catalyst. Moreover, polyisobutylene (PIB) with adjustable Mn  = 20, 000–60, 000 g·mol −1 and relatively narrow molecular weight distribution (MWD) = 2–4 was commonly produced with the complexed catalyst at reaction temperature from −30 to −60 °C. Generally, this complexed catalyst system exhibits remarkable efficiency for IB polymerization, and is endowed with possible industrial relevance for the synthesis of medium molecular weight polyisobutylene (MPIB, Mn  = 10, 000–100, 000 g·mol −1 ).